Azoles, A Potential Anti Diabetic Agents as α- Glucosidase Inhibitors: Past, Current & Future Prospects - Sharma, Deepanshu; Prasad Mishra, Ganesh; Chandra Sharma, Mukesh (Journal of Neonatal Surgery, 2025)
Diabetes is a chronic disordered metabolism disease, indicated by Elevated blood glucose level. Various methods such as Fasting plasma glucose level Oral glucose tolerance test (OGTT) and HbA1c test , have been used to diagnose elevated blood glucose level in the body. A better medication is the only solution to control this disease. For this at present, α-Glucosidase inhibitors are recently used as a first line drug with safer efficacy. During study many previous study it was found that various chemical moieties were involved in the synthesis of α-Glucosidase inhibitors for the treatment of diabetes. Compound bearing azole moiety were one of them. This article compiled various recent researches which involved various types of compounds, having azole in their structure. Our main objective of this article is to focus on such facts, which can be used to design and synthesis of α- Glucosidase inhibitors bearing azole moiety, related to, which will further direct to the researchers in future.